Praperadilan Penetapan Status Tersangka Dalam Dugaan Tindak Pidana Korupsi - Ilham Firdaus; Anak Agung Sagung Laksmi Dewi; NI Made Sukaryati Karma (Jurnal Analogi Hukum, 2020)
Abstract—Pretrial is the authority of the District Court about examining, deciding whether or not the arrest or detention is valid, whether or not the termination of the investigation or termination of the prosecution is legal, and the request for compensation or rehabilitation. The Constitutional Court has determined that new pretrial objects include the validity of the determination of suspects, searches and seizures. This research was conducted, namely to examine the challenges of the Court's decision Number 21 / PID.PRAP / 2017 / PN.DPS regarding the determination of the status of suspects in suspected corruption, while the problem is (1) on the basis of consideration of the judge who canceled the suspect's status? (2) What are the legal consequences of the pretrial decision? In this study, the author uses a normative legal research method and a statutory approach that uses a conceptual approach. The source of legal material is the primary legal material in the form of KUHAP, Law No. 20 of 2001, and Law No.48 of 2009, and secondary legal materials are literature and legal journals that have to do with problems, then analyzed qualitatively and presented in the form of analytical descriptive. The status of the suspect must be based on sufficient initial evidence or preliminary evidence, the provisions clearly stipulated by the Criminal Procedure Code. Determination of suspects in criminal acts of corruption must be proven by the existence of real state financial losses that have existed or arisen meaning, official audits issued by the BPK as a basis or reference to prove the existence of state financial losses (SEMA Number 4 in 2016). Proof and consideration see the absence or absence of sufficient initial evidence, it is not impossible due to the legal determination of the status of the suspect is not valid.